Reconstruction Of Islamic Accounting Theory: A Philosophical Approach Towards the Concepts of Value And Justice - Nehayatul Najwa; Gunawan Aji (Journal of Management, Finance, and Accounting Research, 2025)
This study aims to reconstruct Islamic accounting theory based on the principles of maqashid sharia through a philosophical approach that encompasses ontological, epistemological, and axiological dimensions. Using a conceptual-philosophical method, this study analyzes classical Islamic sources such as the works of Al-Ghazali and Ash-Syatibi, and integrates them with modern accounting theory. The results show that conventional accounting focuses too much on material gain and ignores moral and spiritual accountability, thus losing its ethical orientation. This study produces the Islamic Accounting Maqashid Framework (IAMF) as a conceptual model that places justice (al-‘adl) at the core of accounting practice. The IAMF integrates moral, social, and spiritual dimensions in financial reporting to ensure horizontal accountability to society and vertical accountability to Allah SWT. This framework offers a transformative paradigm for Islamic accounting and provides theoretical and practical implications for financial institutions, auditors, and educational institutions in strengthening ethical and spiritual awareness in accounting practice.